PENGARUH PEMAHAMAN, PENDAPATAN DAN RELIGIUSITAS TERHADAP MINAT UNTUK BERINVESTASI DI PASAR MODAL SYARIAH (Studi Pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIS Sambas) - NURUL NABILA; Iwan Kusnadi (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2020)
Stock investment is an investment activity in a project or company with the aim of obtaining financial benefits in the future. Stocks are investment products that are chosen by many investors because they are able to provide an attractive level of profit. In Islam, investment is a muamalah activity that is highly recommended because by investing the assets you have become productive and also bring benefits to others. This study aims to analyze the effect of understanding, income and religiosity on investment interest in students of the Islamic Economics and Business Faculty Sultan Muhammad Syafiuddin Sambas either partially or simultaneously. This research is a research that uses a quantitative approach with the type of survey research. The data used in the form of primary data obtained through the distribution of questionnaires (questionnaires) to 130 respondents and secondary data in the form of a profile of the research place, namely the Sultan Muhammad Syafiuddin Sambas Islamic Economics and Business Faculty. The primary data obtained were tested with validity, reliability, classical assumption tests and then analyzed using multiple linear regression analysis techniques, T-test and F-test. The results of this study indicate that partially understanding has a positive effect on investment interest in students of the Sultan's Islamic Economics and Business Faculty. Muhammad Syafiuddin Sambas with a coefficient value of 0.393 and a t-count value of 4.487. Income has a positive effect on interest in investing in students of the Islamic Economics and Business Faculty Sultan Muhammad Syafiuddin Sambas with a coefficient value of 0.307 and a t value of 2.549. Meanwhile, religiosity has no effect on interest in investing in students of the Islamic Economics and Business Faculty, Sultan Muhammad Syafiuddin Sambas, with a t-value of 1.349. Simultaneously understanding, income, and religiosity have a positive effect on interest in investing in students of the Islamic Economics and Business Faculty Sultan Muhammad Syafiuddin Sambas with an F count of 23,017.